"Zdaj morate pozabit vse, kar ste se prej naučili" - Jarc, Mojca (Vestnik za tuje jezike, 2015)
The internationalisation of higher education has become a generally acknowledged fact as well as a requirement in the European context. As a result, universities have been faced with increased student mobility and the use of English as a lingua franca. However, students may find themselves in situations in which they cannot or do not want to use English in completing their study obligations at their host institution. In this case, the knowledge of a different foreign language is required for a successful international experience. Issues of students' conception of a foreign academic culture and of being immersed in this culture arise through a perspective of language deficiencies in L3 (students' second foreign language). The aim of this study is to identify obstructions to the successful building of intercultural competences in the specifically francophone environment. Semi-structured interviews were carried out among a group of Slovene undergraduate and graduate social sciences students at a French host institution. Through qualitative text analysis, we examine how Slovene students conceptualise their identity and how they perceive various characteristics of the francophone academic environment. The results suggest that the interviewees' construction of intercultural competences is generally characterised by identity inclusivity, while identity security is obstructed by deficient language skills, incomprehension of academic culture, and feelings of marginalisation in relation to native speakers of the French language. Some pedagogical implications for the development of intercultural competence on the part of language learners at a non-philological faculty are discussed in the final section.
Keywords: mednarodna mobilnost; francoščina; French; strokovni jezik; francoščina kot jezik stroke; medkulturne kompetence; identiteta; frankofona kultura